PRESERVATION OF NATURE IS A NATIONWIDE ISSUE - Ismoilova Gulbaxor Azamovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article is about the situation of forming ecological culture and problems was analyzed among students and its historical process was described.